2021
DOI: 10.3389/fphar.2020.620221
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Effects of Perampanel in Acute and Chronic Pain Models in Mice: Interaction With the Cannabinergic System

Abstract: Pain conditions, such as neuropathic pain (NP) and persistent inflammatory pain are therapeutically difficult to manage. Previous studies have shown the involvement of glutamate receptor in pain modulation and in particular same of these showed the key role of the AMPA ionotropic glutamate receptor subtype. Antiseizure medications (ASMs) are often used to treat this symptom, however the effect of perampanel (PER), an ASM acting as selective, non-competitive inhibitor of the AMPA receptor on the management of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Perampanel, an orally active, noncompetitive, selective AMPAR antagonist, has been widely used for the treatment of epilepsy ( 23 ). Previous studies have revealed that AMPAR antagonists are important potential neuroprotective agents in preclinical models of ischemic stroke ( 39 ), spinal cord injury ( 40 ), and traumatic brain injury ( 27 ). However, while these early studies revealed that AMPAR antagonists could minimize brain injury and neuronal death following ICH, the potential molecular mechanisms and consequent effects were not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Perampanel, an orally active, noncompetitive, selective AMPAR antagonist, has been widely used for the treatment of epilepsy ( 23 ). Previous studies have revealed that AMPAR antagonists are important potential neuroprotective agents in preclinical models of ischemic stroke ( 39 ), spinal cord injury ( 40 ), and traumatic brain injury ( 27 ). However, while these early studies revealed that AMPAR antagonists could minimize brain injury and neuronal death following ICH, the potential molecular mechanisms and consequent effects were not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral pain tends to company physical discomfort and special positions like knee flexion position in humans. Similarly, the number of writhes in a certain period reflects the degree of pain in rats and is often used in pain-model experiments [ 44 46 ]. Acute visceral pain like acute appendicitis tends to lead to superficial or deep hyperalgesia or allodynia [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6, IL-1β, and IL-2 are involved in many in ammatory visceral pain diseases like visceral pain after surgery, endometriosis [40,41]. Nalbuphine is applied in some clinical researches to play valid antiin ammatory and analgesic effects [42,43]. Excepting in the clinical studies, in ML's study, expressions of pro-in ammatory cytokines (IL-6, IL-1β, and TNF-α) in the spinal cord tissues were increased in visceral pain rats and inhibited by dexmedetomidine [44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the number of writhes in a certain period re ects the degree of pain in rats and is often used in pain-model experiments [41][42][43]. Acute visceral pain like acute appendicitis tends to lead to super cial or deep hyperalgesia or allodynia [44].…”
Section: Discussionmentioning
confidence: 99%